Respostas
respondido por:
1
Ola Junior
4x³ - 16x² - x + m = 0
a soma das raízes é -b/a = 16/4 = 4
duas raízes opostas x1 + x2 = 0
S = x1 + x2 + x3 = 0 + x3 = 4
x3 = 4
4x³ - 16x² - x + m = 0
4*4³ - 16*4² - 4 + m = 0
256 - 256 - 4 + m
m = 4 (C)
.
4x³ - 16x² - x + m = 0
a soma das raízes é -b/a = 16/4 = 4
duas raízes opostas x1 + x2 = 0
S = x1 + x2 + x3 = 0 + x3 = 4
x3 = 4
4x³ - 16x² - x + m = 0
4*4³ - 16*4² - 4 + m = 0
256 - 256 - 4 + m
m = 4 (C)
.
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás